Humidophila komarekiana sp. nov. (Bacillariophyta), a new limnoterrestrial diatom species from King George Island (Maritime Antarctica) - Kochman-Kędziora, Natalia; Noga, Teresa; Zidarova, Ralitsa; Kopalová, Kateřina; van De Vijver, Bart (Phytotaxa, 2016)
During a survey of the non-marine diatom flora of King George Island (South Shetland Islands), an unknown Humidophila taxon was recorded. Detailed light and scanning electron microscopy observations indicated that the unknown taxon could not be identified based on the currently available literature. The new species is described as Humidophila komarekiana sp. nov. and is characterized in having strictly linear valves with parallel margins and broadly rounded, never protracted apices, a filiform raphe with almost indistinct, straight proximal and distal raphe endings. The striae are composed of one, irregularly shortened areola. The mantle areolae are interrupted at the apices. The new species is compared with similar taxa in the Antarctic Region and worldwide. Notes on the ecology of the new species are added.